IMMUNOPROPHYLAXIS OF SEVERE RESPIRATORY-SYNCYTIAL VIRAL INFECTION IN CHILDREN WITH BRONCHOPULMONARY DYSPLASIA: RESULTS OF 4 EPIDEMIC SEASONS - A. A. Baranov; I. V. Davydova; T. V. Turti; L. S. Namazova-Baranova; V. V. Altunin; E. P. Zimina; E. V. Pavlyukova (Педиатрическая фармакология, 2012)
Children with bronchopulmonary dysplasia belong to the risk group of severe respiratory-syncytial viral infection (RSV). World experience and authors' own clinical data show that seasonal immunoprophylaxis of RSV infection's severe course by palivizumab in these patients allows reducing frequency of hospitalizations, CPR conduct and fatal outcomes. The article gives data of clinical instrumental evaluation of efficacy and safety of palivizumab use in the 3 past and the 4th (current) epidemic seasons.